Idiopathic chest pain in Division I collegiate track and field athlete: A case study - Grimshaw, A.; Joseph, C. (Journal of Athletic Training, 2019)
Background: The athlete is a 20-year-old female, African American, Division I track and fi eld student athlete. On January 11th, the athlete traveled to an out of state track meet. After arriving, she presented with cough, congestion, headache, sore throat and fatigue. Over the counter medication was administered for her symptoms. Hours after competing in her race on January 12th, she presented with body aches, labored breathing, chest pain, fever, and cough. Previous medical history consists of pneumonia and asthma diagnoses a year and a half prior. The athlete is a nonsmoker with no family history of lung disease. Differential Diagnosis: Pneumonia in right middle lobe (RML) with partial atelectasis from apparent right bronchus intermedius (RBI) endobronchial lesion; carcinoid tumor; mucus plug obstructing the RML; acute bronchospasm; allergic bronchopulmonary aspergillosis; influenza. Treatment: On January 12th, the athlete was transported to the local emergency room where she was treated with Tamifl u despite a negative fl u screen, Solu-Medrol, Duonebs, doxycycline, ceftriaxone, and Toradol. An initial chest X-ray (CXR) concluded questionable right basilar airspace opacity. A CT angiogram detected an endobronchial mass in the RML with secondary multi-segmental atelectasis and pneumonia. Due to prolonged symptoms, she was admitted into the intensive care unit (ICU) on January 13th and continued the use of antibiotics, breathing treatments, and intravenous fluids. A second CXR showed the RML airspace had become more apparent. On January 15th, a bronchoscopy showed the RBI was 80% obscured by an endobronchial tumor arising from the RML takeoff. The RML was completely obstructed by the tumor, but the right lower lobe (RLL) appeared to be open. All tumor cells were negative for malignancy, which confi rmed the diagnosis of a carcinoid tumor. On January 16th, the athlete was discharged from the ICU and the local pulmonologist cleared her to fl y home to her university. Immediate consultation was advised with a pulmonologist in Orlando to resect the tumor. On January 26th, the athlete was seen by a thoracic surgeon for consultation and had surgery on February 1st. The athlete underwent a bronchoscopy and roboticassisted right middle lobectomy with bronchoplastic resection and anastomosis of the RLL and mediastinal lymph node dissection. Five weeks postoperation, the athlete began light cardiovascular activity. On April 2nd, she started progressing into full participation in practice. She made a full return to athletics as a Division I collegiate track and fi eld athlete. Uniqueness: Her projected surgical plan included the resection of the RML and RLL, but her RLL was preserved during surgery. There was no expectation to return to her sport based on the original bronchoscopy fi ndings. She is still competing as a Division I scholarship track sprinter. Twenty percent of carcinoid tumors are found in the lungs and account for 1-2% of lung cancers. Lung carcinoid tumors are most commonly found in Caucasians and adults between the ages of 45 and 55. Twenty-five percent of patients do not experience symptoms and the tumor is unlikely to metastasize. Conclusions:Symptoms presented very abruptly and the time from initial presentation to surgery was three weeks. Full recovery for this student athlete was three months, but the time to full recovery depends on symptoms and the amount of lung tissue disrupted during surgery. The removal of the RML is not a medical disqualifi er for athletic participation. By preserving the RLL during surgery, the athlete was able to maintain an appropriate total lung volume to continue in athletics.